A contribution to the classification of cases of non-classic 21-hydroxylase-deficient congenital adrenal hyperplasia - Phocas, I.; Chryssikopoulos, A.; Sarandakou, A.; Rizos, D.; Trakakis, E. (Gynecological Endocrinology, 1995)
The aim of this study was to classify the degree of 21αhydroxylase deficiency in patients suspected for non-classic 21-hydroxylase-deficient congenital adrenal hyperplasia (CAH). In 66 selected subjects (45 young women with polycystic ovary (PCO)-like symptoms and members of their families, of whom 12 were men), progesterone, 17-hydroxyprogesterone (17-OHP) and cortisol were measured at 0, 15, 30, 45 and 60 min after adrenocorticotropic hormone (ACTH) stimulation. The markers [(17-OHP at 30 min - 17-OHP at 0 min) + (progesterone at 30 min - progesterone at 0 min)]/30 proposed by Gutai and the ratio of cortisol to 17-OHP at 30 min (cortisol30/17-OHP30) were calculated and cluster analysis was performed using the above two markers and 17-OHP at 60 min (17-OHP60). Our patients were grouped by cluster analysis into four Groups: I, II, III and IV (n = 3, 11, 35 and 16, respectively) with (1) Gutai (x±SE) 107.0±21.7, 29.9±4.4, 10.5±0.54 and 4.0±0.37 ng/dl per min, respectively, (2) 17-OHP60 169.7±28.3, 10.8±1.3, 4.6±0.2 and 3.7±0.4 ng/ml, respectively, and (3) cortisol/17-OHP30 0.97±0.28, 38.5±6.9, 82.3±5.5 and 112.0±8.9, respectively. All three markers showed highly significant differences between the four groups (p < 0.0001). The patterns of 17-OHP, cortisol and cortisol/17-OHP ratio following ACTH testing revealed the degree of 21-hydroxylase deficiency in every group. HLA typing effected in 20 studied individuals confirmed the classification derived from cluster analysis. Thus, it seems that Groups I, II and III include, respectively, patients with severe, mild and minimal forms of non-classic 21-hydroxylase-deficient CAH, while in patients of Group IV the hyperandrogenemic symptoms are of different etiology. In conclusion, the concurrent evaluation of the three markers together with the variations of 17-OHP, cortisol and the cortisol/17-OHP ratio after ACTH testing enhance the accurate identification of a patient suspected for non-classic 21-hydroxylase-deficient CAH in relation to the severity of the enzymatic defect. © 1995 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
Keywords: 17-Hydroxyprogesterone; ACTH Stimulation; Biochemical and Clinical Phenotype; Cluster analysis; Cortisol; Cortisol/17-Hydroxyprogesterone Ratio; Non-Classic 21-Hydroxylase Deficiency